Products and services for the private sector - World Bank Group; Business Partnership Center (Washington, D.C. : World Bank Group, 1998)
Introduction to various World Bank Group institutions and their products and services. Covers procurement opportunities, debt and equity financing, loan syndications, country and market data, political risk insurance, guarantees, advisory services, and special resources online.
Presented by Business Partnership Center.
System requirements for PC: 12MB RAM or more; Windows 3.1 or later, Windows 95, or Windows 98; Quicktime 2.1 or later; sound card; CD-ROM drive.
Keywords: World Bank Group